Waterproof oil-resistant modified rubber sheath material
By compounding components such as nitrile rubber and fluororubber, and combining them with nanomaterials and composite modifiers, a waterproof and oil-resistant modified rubber sheath material was prepared. This solved the problem of insufficient performance of traditional sheath materials in harsh environments, and achieved excellent waterproof and oil-resistant properties as well as a simple preparation process.
Patent Information
- Application Number
- CN202511282740.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-09
- Publication Date
- 2025-10-28
AI Technical Summary
Traditional rubber sheath materials have deficiencies in waterproof and oil resistance, especially in harsh environments where their performance degrades significantly, affecting the safety and service life of cables and wires.
Waterproof and oil-resistant modified rubber sheath material is prepared by using components such as nitrile rubber, fluororubber, nano-boron titanium-silane composite modifier, perfluoropolyether-polyurethane copolymer, and graphene-carbon nanotube composite conductive filler through plasticizing, mixing, thin-passing and vulcanization processes.
It improves the waterproof performance, oil resistance, mechanical strength, and ease of preparation of the sheath material, making it suitable for large-scale industrial production.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of rubber material technology, specifically a waterproof and oil-resistant modified rubber sheath material. Background Technology
[0002] In the fields of cables and wires, rubber sheathing materials play a crucial role in protecting the internal structure from external environmental influences. However, traditional rubber sheathing materials are insufficient in terms of waterproofing and oil resistance, especially in harsh working environments such as humid and oily conditions, where their performance significantly deteriorates, leading to aging and cracking of the sheathing material, thereby affecting the safety and service life of cables and wires. Although some modified rubber sheathing materials exist in the current technology, they often suffer from drawbacks such as limited performance, poor overall performance, or complex manufacturing processes, failing to meet increasingly stringent usage requirements. Therefore, developing a modified rubber sheathing material that combines excellent waterproofing and oil resistance with a simple manufacturing process is of significant practical importance.
[0003] Based on this, a waterproof and oil-resistant modified rubber sheath material was designed. Summary of the Invention
[0004] In view of the above situation and to overcome the defects of the prior art, the present invention provides a waterproof and oil-resistant modified rubber sheath material and its preparation method, which effectively solves the problems mentioned in the background.
[0005] To achieve the above objectives, the present invention provides the following technical solution: a waterproof and oil-resistant modified rubber sheath material, comprising the following components in parts by weight:
[0006] Nitrile rubber: 80-100 parts;
[0007] Fluororubber: 20-30 parts;
[0008] Nano-titanium boride-silane composite modifier: 5-10 parts;
[0009] Perfluoropolyether-polyurethane copolymer: 8-15 parts;
[0010] Graphene-carbon nanotube composite conductive filler: 3-6 parts;
[0011] Zinc oxide: 3-5 parts;
[0012] Sulfur: 1-2 parts;
[0013] Accelerator DM: 1-2 parts;
[0014] Accelerator TMTD: 0.5-1 part;
[0015] Quickly press out carbon black: 15-20 parts;
[0016] Nano calcium carbonate: 10-15 parts;
[0017] Dibutyl phthalate: 8-12 parts;
[0018] Dioctyl sebacate: 5-8 parts;
[0019] Anti-aging agent MB: 0.5-1 part;
[0020] Anti-aging agent 4010NA: 0.5-1 part.
[0021] Preferably, the preparation method of the nano-titanium boride-silane composite modifier is as follows:
[0022] S1. Pretreatment of nano-titanium boride: Place nano-titanium boride powder in an oven and dry it at 100-120℃ for 2-3 hours to remove surface moisture;
[0023] S2. Preparation of silane solution: Weigh a certain amount of γ-aminopropyltriethoxysilane and add it to anhydrous ethanol to prepare a silane solution with a mass fraction of 5%-10%.
[0024] S3. Composite Modification: The pretreated nano-titanium boride powder is slowly added to a silane solution at a solid-liquid ratio of 1:10. The mixture is stirred at 200-300 r / min for 3-4 hours at 50-60℃ to allow the silane to be fully adsorbed onto the surface of the nano-titanium boride. Then, the mixture is filtered and washed 3-5 times with anhydrous ethanol to remove unreacted silane. Finally, the washed product is dried at 80-90℃ for 2-3 hours to obtain the nano-titanium boride-silane composite modifier.
[0025] Preferably, the preparation method of the perfluoropolyether-polyurethane copolymer is as follows:
[0026] S1. Raw material preparation: Weigh a certain amount of perfluoropolyether diol, polyether polyol and toluene diisocyanate. The mass ratio of perfluoropolyether diol to polyether polyol is 1:2-3. The amount of toluene diisocyanate used is 1.2-1.5 times the total mass of perfluoropolyether diol and polyether polyol.
[0027] S2. Prepolymerization reaction: Add perfluoropolyether diol and polyether polyol to a three-necked flask, heat to 80-90℃ under nitrogen protection, stir to melt and mix evenly; then, slowly add toluene diisocyanate, react at 80-90℃ for 2-3 hours to obtain the prepolymer;
[0028] S3. Chain extension reaction: Cool the prepolymer to 50-60℃, add chain extender 1,4-butanediol, the amount of which is 10%-15% of the prepolymer mass, and continue the reaction for 1-2 hours to further polymerize the prepolymer and obtain perfluoropolyether-polyurethane copolymer.
[0029] Preferably, the preparation method of the graphene-carbon nanotube composite conductive filler is as follows:
[0030] S1. Dispersion of graphene and carbon nanotubes: Weigh a certain amount of graphene and carbon nanotubes respectively, add them to N,N-dimethylformamide at a mass ratio of 2:1, and ultrasonically disperse them in an ultrasonic cleaner at a frequency of 40-50kHz for 1-2 hours to obtain a uniform graphene dispersion and carbon nanotube dispersion.
[0031] S2. Composite reaction: Mix the graphene dispersion and the carbon nanotube dispersion, and stir at 150-200 r / min for 2-3 hours at 60-70℃ to fully composite the graphene and carbon nanotubes; then, filter the mixture and wash it 3-5 times with N,N-dimethylformamide to remove unreacted impurities; finally, dry the washed product at 80-90℃ for 2-3 hours to obtain the graphene-carbon nanotube composite conductive filler.
[0032] Preferably, the preparation method of the waterproof and oil-resistant modified rubber sheath material is as follows:
[0033] S1. Plasticizing: Place nitrile rubber and fluororubber into a plasticizing machine and plasticize at 90-100℃ for 5-8 minutes to give the rubber a certain degree of plasticity.
[0034] S2. Mixing: Place the plasticized rubber into a mixer and add nano-titanium boride-silane composite modifier, perfluoropolyether-polyurethane copolymer, graphene-carbon nanotube composite conductive filler, fast-extrusion carbon black, nano-calcium carbonate, dibutyl phthalate, and dioctyl sebacate in sequence. Mix at 80-90℃ for 8-10 minutes to ensure that all raw materials are fully and evenly mixed.
[0035] S3. Add vulcanization system and antioxidant: Add zinc oxide, sulfur, accelerator DM, accelerator TMTD, antioxidant MB, and antioxidant 4010NA to the internal mixer and continue mixing for 3-5 minutes to ensure that the vulcanization system and antioxidant are evenly dispersed in the rubber.
[0036] S4, thin pass and calendering: The mixed rubber is put into the open mill for thin pass 5-7 times, and then calendered into sheet of the required thickness by a three-roll calender.
[0037] S5. Vulcanization: Place the calendered sheet into a flat vulcanizing machine and vulcanize it for 8-10 minutes at 160-170℃ and 10-12MPa to obtain waterproof and oil-resistant modified rubber sheath material.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] 1. This invention has excellent waterproof performance. The addition of perfluoropolyether-polyurethane copolymer forms a dense waterproof film on the surface of the sheath material, which effectively prevents water penetration and improves the waterproof performance of the sheath material.
[0040] 2. This invention has good oil resistance. The synergistic effect of nano-titanium boride-silane composite modifier and graphene-carbon nanotube composite conductive filler enhances the chemical stability of rubber and oil media and improves the oil resistance of the sheath material.
[0041] 3. This invention has high mechanical strength. The addition of nanomaterials such as nano-titanium boride, graphene and carbon nanotubes fills the gaps between rubber molecules and forms a three-dimensional network structure, which significantly improves the mechanical strength and wear resistance of the sheath material.
[0042] 4. The preparation process is simple. The preparation method of the present invention is simple to operate, easy to control, and suitable for large-scale industrial production. Detailed Implementation
[0043] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0044] This invention provides a waterproof and oil-resistant modified rubber sheath material, comprising the following components in parts by weight:
[0045] Nitrile rubber: 80-100 parts;
[0046] Fluororubber: 20-30 parts;
[0047] Nitrile rubber has good oil resistance, while fluororubber has excellent chemical corrosion resistance and high temperature resistance. The combination of the two can play a synergistic role and improve the overall performance of the sheath material.
[0048] Nano-titanium boride-silane composite modifier: 5-10 parts;
[0049] This component significantly improves the mechanical strength and oil resistance of rubber through composite modification of nano-titanium boride and silane. Nano-titanium boride has high hardness, high strength and good chemical stability, while silane can improve the compatibility between nano-titanium boride and rubber matrix and enhance interfacial bonding.
[0050] Perfluoropolyether-polyurethane copolymer: 8-15 parts;
[0051] Perfluoropolyether has extremely low surface energy, giving the sheath material excellent waterproof performance; polyurethane can improve the material's flexibility and abrasion resistance; the copolymer formed by the copolymerization of the two combines the waterproofness of perfluoropolyether and the flexibility of polyurethane.
[0052] Graphene-carbon nanotube composite conductive filler: 3-6 parts;
[0053] Both graphene and carbon nanotubes have excellent electrical and mechanical properties. When combined, they can form a three-dimensional conductive network, which can improve the conductivity of the sheath material while enhancing its mechanical strength and oil resistance.
[0054] Zinc oxide: 3-5 parts;
[0055] Sulfur: 1-2 parts;
[0056] Accelerator DM: 1-2 parts;
[0057] Accelerator TMTD: 0.5-1 part;
[0058] Zinc oxide, sulfur, accelerator DM, and accelerator TMTD form a vulcanization system that promotes cross-linking reactions between rubber molecules, thereby improving the physical and mechanical properties and aging resistance of rubber.
[0059] Quickly press out carbon black: 15-20 parts;
[0060] Nano calcium carbonate: 10-15 parts;
[0061] Rapidly extruded carbon black and nano-calcium carbonate are used as reinforcing fillers to fill the gaps between rubber molecules, thereby improving the strength and wear resistance of rubber.
[0062] Dibutyl phthalate: 8-12 parts;
[0063] Dioctyl sebacate: 5-8 parts;
[0064] Dibutyl phthalate and dioctyl sebacate are plasticizers that can lower the glass transition temperature of rubber and improve its flexibility and processing performance.
[0065] Anti-aging agent MB: 0.5-1 part;
[0066] Anti-aging agent 4010NA: 0.5-1 part;
[0067] Antioxidant MB and Antioxidant 4010NA can inhibit the aging reaction of rubber under the influence of environmental factors such as light, heat, and oxygen, and extend the service life of rubber.
[0068] The preparation method of the nano-titanium boride-silane composite modifier in this embodiment is as follows:
[0069] S1. Pretreatment of nano-titanium boride: Place nano-titanium boride powder in an oven and dry it at 100-120℃ for 2-3 hours to remove surface moisture;
[0070] S2. Preparation of silane solution: Weigh a certain amount of γ-aminopropyltriethoxysilane and add it to anhydrous ethanol to prepare a silane solution with a mass fraction of 5%-10%.
[0071] S3. Composite Modification: The pretreated nano-titanium boride powder is slowly added to a silane solution at a solid-liquid ratio of 1:10. The mixture is stirred at 200-300 r / min for 3-4 hours at 50-60℃ to allow the silane to be fully adsorbed onto the surface of the nano-titanium boride. Then, the mixture is filtered and washed 3-5 times with anhydrous ethanol to remove unreacted silane. Finally, the washed product is dried at 80-90℃ for 2-3 hours to obtain the nano-titanium boride-silane composite modifier.
[0072] The preparation method of the perfluoropolyether-polyurethane copolymer in this embodiment is as follows:
[0073] S1. Raw material preparation: Weigh a certain amount of perfluoropolyether diol, polyether polyol and toluene diisocyanate. The mass ratio of perfluoropolyether diol to polyether polyol is 1:2-3. The amount of toluene diisocyanate used is 1.2-1.5 times the total mass of perfluoropolyether diol and polyether polyol.
[0074] S2. Prepolymerization reaction: Add perfluoropolyether diol and polyether polyol to a three-necked flask, heat to 80-90℃ under nitrogen protection, stir to melt and mix evenly; then, slowly add toluene diisocyanate, react at 80-90℃ for 2-3 hours to obtain the prepolymer;
[0075] S3. Chain extension reaction: Cool the prepolymer to 50-60℃, add chain extender 1,4-butanediol, the amount of which is 10%-15% of the prepolymer mass, and continue the reaction for 1-2 hours to further polymerize the prepolymer and obtain perfluoropolyether-polyurethane copolymer.
[0076] The preparation method of the graphene-carbon nanotube composite conductive filler in this embodiment is as follows:
[0077] S1. Dispersion of graphene and carbon nanotubes: Weigh a certain amount of graphene and carbon nanotubes respectively, add them to N,N-dimethylformamide at a mass ratio of 2:1, and ultrasonically disperse them in an ultrasonic cleaner at a frequency of 40-50kHz for 1-2 hours to obtain a uniform graphene dispersion and carbon nanotube dispersion.
[0078] S2. Composite reaction: Mix the graphene dispersion and the carbon nanotube dispersion, and stir at 150-200 r / min for 2-3 hours at 60-70℃ to fully composite the graphene and carbon nanotubes; then, filter the mixture and wash it 3-5 times with N,N-dimethylformamide to remove unreacted impurities; finally, dry the washed product at 80-90℃ for 2-3 hours to obtain the graphene-carbon nanotube composite conductive filler.
[0079] The preparation method of the waterproof and oil-resistant modified rubber sheath material in this embodiment is as follows:
[0080] S1. Plasticizing: Place nitrile rubber and fluororubber into a plasticizing machine and plasticize at 90-100℃ for 5-8 minutes to give the rubber a certain degree of plasticity.
[0081] S2. Mixing: Place the plasticized rubber into a mixer and add nano-titanium boride-silane composite modifier, perfluoropolyether-polyurethane copolymer, graphene-carbon nanotube composite conductive filler, fast-extrusion carbon black, nano-calcium carbonate, dibutyl phthalate, and dioctyl sebacate in sequence. Mix at 80-90℃ for 8-10 minutes to ensure that all raw materials are fully and evenly mixed.
[0082] S3. Add vulcanization system and antioxidant: Add zinc oxide, sulfur, accelerator DM, accelerator TMTD, antioxidant MB, and antioxidant 4010NA to the internal mixer and continue mixing for 3-5 minutes to ensure that the vulcanization system and antioxidant are evenly dispersed in the rubber.
[0083] S4, thin pass and calendering: The mixed rubber is put into the open mill for thin pass 5-7 times, and then calendered into sheet of the required thickness by a three-roll calender.
[0084] S5. Vulcanization: Place the calendered sheet into a flat vulcanizing machine and vulcanize it for 8-10 minutes at 160-170℃ and 10-12MPa to obtain waterproof and oil-resistant modified rubber sheath material.
[0085] Example 1:
[0086] A waterproof and oil-resistant modified rubber sheath material comprises the following components in parts by weight:
[0087] Nitrile rubber: 80 parts;
[0088] Fluororubber: 20 parts;
[0089] Nano-titanium boride-silane composite modifier: 5 parts;
[0090] Perfluoropolyether-polyurethane copolymer: 8 parts;
[0091] Graphene-carbon nanotube composite conductive filler: 3 parts;
[0092] Zinc oxide: 3 parts;
[0093] Sulfur: 1 part;
[0094] Accelerator DM: 1 part;
[0095] Accelerator TMTD: 0.5 parts;
[0096] Quickly press out carbon black: 15 parts;
[0097] Nano calcium carbonate: 10-15 parts;
[0098] Dibutyl phthalate: 8 parts;
[0099] Dioctyl sebacate: 5 parts;
[0100] Anti-aging agent MB: 0.5 parts;
[0101] Antioxidant 4010NA: 0.5 parts.
[0102] The preparation method of the nano-titanium boride-silane composite modifier in this embodiment is as follows:
[0103] S1. Pretreatment of nano-titanium boride: Place nano-titanium boride powder in an oven and dry at 100℃ for 2 hours to remove surface moisture;
[0104] S2. Preparation of silane solution: Weigh a certain amount of γ-aminopropyltriethoxysilane and add it to anhydrous ethanol to prepare a 5% silane solution by mass.
[0105] S3. Composite Modification: The pretreated nano-titanium boride powder was slowly added to a silane solution at a solid-liquid ratio of 1:10. The mixture was stirred at 200 r / min for 3 hours at 50°C to allow the silane to be fully adsorbed onto the surface of the nano-titanium boride. The mixture was then filtered and washed three times with anhydrous ethanol to remove unreacted silane. Finally, the washed product was dried at 80°C for 2 hours to obtain the nano-titanium boride-silane composite modifier.
[0106] The preparation method of the perfluoropolyether-polyurethane copolymer in this embodiment is as follows:
[0107] S1. Raw material preparation: Weigh a certain amount of perfluoropolyether diol, polyether polyol and toluene diisocyanate. The mass ratio of perfluoropolyether diol to polyether polyol is 1:2. The amount of toluene diisocyanate used is 1.2 times the total mass of perfluoropolyether diol and polyether polyol.
[0108] S2. Prepolymerization reaction: Perfluoropolyether diol and polyether polyol are added to a three-necked flask and heated to 80°C under nitrogen protection. The mixture is stirred until it melts and is mixed evenly. Then, toluene diisocyanate is slowly added dropwise and the mixture is reacted at 80°C for 2 hours to obtain the prepolymer.
[0109] S3. Chain extension reaction: Cool the prepolymer to 50°C, add chain extender 1,4-butanediol, the amount of which is 10% of the prepolymer mass, and continue the reaction for 1 hour to further polymerize the prepolymer to obtain perfluoropolyether-polyurethane copolymer.
[0110] The preparation method of the graphene-carbon nanotube composite conductive filler in this embodiment is as follows:
[0111] S1. Dispersion of graphene and carbon nanotubes: Weigh a certain amount of graphene and carbon nanotubes respectively, add them to N,N-dimethylformamide at a mass ratio of 2:1, and ultrasonically disperse them in an ultrasonic cleaner at a frequency of 40kHz for 1 hour to obtain a uniform graphene dispersion and carbon nanotube dispersion.
[0112] S2. Composite reaction: The graphene dispersion and carbon nanotube dispersion were mixed and stirred at 150 r / min for 2 hours at 60℃ to fully composite the graphene and carbon nanotubes. Then, the mixture was filtered and washed three times with N,N-dimethylformamide to remove unreacted impurities. Finally, the washed product was dried at 80℃ for 2 hours to obtain the graphene-carbon nanotube composite conductive filler.
[0113] The preparation method of the waterproof and oil-resistant modified rubber sheath material in this embodiment is as follows:
[0114] S1. Plasticizing: Place nitrile rubber and fluororubber into a plasticizing machine and plasticize at 90°C for 5 minutes to give the rubber a certain degree of plasticity.
[0115] S2. Mixing: Put the plasticized rubber into a mixer and add nano-titanium boride-silane composite modifier, perfluoropolyether-polyurethane copolymer, graphene-carbon nanotube composite conductive filler, fast-extrusion carbon black, nano-calcium carbonate, dibutyl phthalate, and dioctyl sebacate in sequence. Mix at 80°C for 8 minutes to ensure that all raw materials are fully and evenly mixed.
[0116] S3. Add vulcanization system and antioxidant: Add zinc oxide, sulfur, accelerator DM, accelerator TMTD, antioxidant MB, and antioxidant 4010NA to the internal mixer and continue mixing for 3 minutes to ensure that the vulcanization system and antioxidant are evenly dispersed in the rubber.
[0117] S4, thin pass and calendering: The mixed rubber is put into the open mill and thin pass 5 times, and then calendered into sheet of the required thickness by a three-roll calender.
[0118] S5. Vulcanization: Place the calendered sheet into a flat vulcanizing machine and vulcanize it for 8-10 minutes at 160℃ and 10MPa to obtain waterproof and oil-resistant modified rubber sheath material.
[0119] Example 2:
[0120] A waterproof and oil-resistant modified rubber sheath material comprises the following components in parts by weight:
[0121] Nitrile rubber: 100 parts;
[0122] Fluororubber: 30 parts;
[0123] Nano-titanium boride-silane composite modifier: 10 parts;
[0124] Perfluoropolyether-polyurethane copolymer: 15 parts;
[0125] Graphene-carbon nanotube composite conductive filler: 6 parts;
[0126] Zinc oxide: 5 parts;
[0127] Sulfur: 2 parts;
[0128] Accelerator DM: 2 parts;
[0129] Accelerator TMTD: 1 part;
[0130] Quickly press out carbon black: 20 parts;
[0131] Nano-calcium carbonate: 15 parts;
[0132] Dibutyl phthalate: 12 parts;
[0133] Dioctyl sebacate: 8 parts;
[0134] Anti-aging agent MB: 1 part;
[0135] Anti-aging agent 4010NA: 1 part.
[0136] The preparation method of the nano-titanium boride-silane composite modifier in this embodiment is as follows:
[0137] S1. Pretreatment of nano-titanium boride: Place nano-titanium boride powder in an oven and dry at 120℃ for 3 hours to remove surface moisture;
[0138] S2. Preparation of silane solution: Weigh a certain amount of γ-aminopropyltriethoxysilane and add it to anhydrous ethanol to prepare a 10% silane solution by mass.
[0139] S3. Composite Modification: The pretreated nano-titanium boride powder was slowly added to a silane solution at a solid-liquid ratio of 1:10. The mixture was stirred at 300 r / min for 4 hours at 60°C to allow the silane to be fully adsorbed onto the surface of the nano-titanium boride. The mixture was then filtered and washed five times with anhydrous ethanol to remove unreacted silane. Finally, the washed product was dried at 90°C for 3 hours to obtain the nano-titanium boride-silane composite modifier.
[0140] The preparation method of the perfluoropolyether-polyurethane copolymer in this embodiment is as follows:
[0141] S1. Raw material preparation: Weigh a certain amount of perfluoropolyether diol, polyether polyol and toluene diisocyanate. The mass ratio of perfluoropolyether diol to polyether polyol is 1:3. The amount of toluene diisocyanate used is 1.5 times the total mass of perfluoropolyether diol and polyether polyol.
[0142] S2. Prepolymerization reaction: Perfluoropolyether diol and polyether polyol are added to a three-necked flask and heated to 90°C under nitrogen protection. The mixture is stirred until it melts and is mixed evenly. Then, toluene diisocyanate is slowly added dropwise and the mixture is reacted at 90°C for 3 hours to obtain the prepolymer.
[0143] S3. Chain extension reaction: Cool the prepolymer to 60°C, add chain extender 1,4-butanediol, the amount of which is 15% of the mass of the prepolymer, and continue the reaction for 2 hours to further polymerize the prepolymer to obtain perfluoropolyether-polyurethane copolymer.
[0144] The preparation method of the graphene-carbon nanotube composite conductive filler in this embodiment is as follows:
[0145] S1. Dispersion of graphene and carbon nanotubes: Weigh a certain amount of graphene and carbon nanotubes respectively, add them to N,N-dimethylformamide at a mass ratio of 2:1, and ultrasonically disperse them in an ultrasonic cleaner at a frequency of 50kHz for 2 hours to obtain a uniform graphene dispersion and carbon nanotube dispersion.
[0146] S2. Composite reaction: The graphene dispersion and carbon nanotube dispersion were mixed and stirred at 200 r / min for 3 hours at 70℃ to fully composite the graphene and carbon nanotubes. Then, the mixture was filtered and washed 5 times with N,N-dimethylformamide to remove unreacted impurities. Finally, the washed product was dried at 90℃ for 3 hours to obtain the graphene-carbon nanotube composite conductive filler.
[0147] The preparation method of the waterproof and oil-resistant modified rubber sheath material in this embodiment is as follows:
[0148] S1. Plasticizing: Place nitrile rubber and fluororubber into a plasticizing machine and plasticize at 100°C for 8 minutes to give the rubber a certain degree of plasticity.
[0149] S2. Mixing: Place the plasticized rubber into a mixer and add nano-titanium boride-silane composite modifier, perfluoropolyether-polyurethane copolymer, graphene-carbon nanotube composite conductive filler, fast-extrusion carbon black, nano-calcium carbonate, dibutyl phthalate, and dioctyl sebacate in sequence. Mix at 90°C for 10 minutes to ensure that all raw materials are fully and evenly mixed.
[0150] S3. Add vulcanization system and antioxidant: Add zinc oxide, sulfur, accelerator DM, accelerator TMTD, antioxidant MB, and antioxidant 4010NA to the internal mixer and continue mixing for 5 minutes to ensure that the vulcanization system and antioxidant are evenly dispersed in the rubber.
[0151] S4, thin pass and calendering: The mixed rubber is put into the open mill and thin pass 7 times, and then calendered into sheet of the required thickness by a three-roll calender.
[0152] S5. Vulcanization: The calendered sheet is placed in a flat vulcanizing machine and vulcanized for 10 minutes at 170℃ and 12MPa to obtain a waterproof and oil-resistant modified rubber sheath material.
[0153] Example 3:
[0154] A waterproof and oil-resistant modified rubber sheath material comprises the following components in parts by weight:
[0155] Nitrile rubber: 90 parts;
[0156] Fluororubber: 25 parts;
[0157] Nano-titanium boride-silane composite modifier: 7.5 parts;
[0158] Perfluoropolyether-polyurethane copolymer: 11.5 parts;
[0159] Graphene-carbon nanotube composite conductive filler: 4.5 parts;
[0160] Zinc oxide: 4 parts;
[0161] Sulfur: 1.5 parts;
[0162] Accelerator DM: 1.5 parts;
[0163] Accelerator TMTD: 0.8 parts;
[0164] Fast-pressed carbon black: 17.5 parts;
[0165] Nano-calcium carbonate: 12.5 parts;
[0166] Dibutyl phthalate: 10 parts;
[0167] Dioctyl sebacate: 6.5 parts;
[0168] Anti-aging agent MB: 0.8 parts;
[0169] Antioxidant 4010NA: 0.8 parts.
[0170] The preparation method of the nano-titanium boride-silane composite modifier in this embodiment is as follows:
[0171] S1. Pretreatment of nano-titanium boride: Place nano-titanium boride powder in an oven and dry at 110℃ for 2.5 hours to remove surface moisture;
[0172] S2. Preparation of silane solution: Weigh a certain amount of γ-aminopropyltriethoxysilane and add it to anhydrous ethanol to prepare a silane solution with a mass fraction of 7.5%.
[0173] S3. Composite Modification: The pretreated nano-titanium boride powder was slowly added to a silane solution at a solid-liquid ratio of 1:10. The mixture was stirred at 250 r / min for 3.5 hours at 55°C to allow the silane to be fully adsorbed onto the surface of the nano-titanium boride. The mixture was then filtered and washed four times with anhydrous ethanol to remove unreacted silane. Finally, the washed product was dried at 85°C for 2.5 hours to obtain the nano-titanium boride-silane composite modifier.
[0174] The preparation method of the perfluoropolyether-polyurethane copolymer in this embodiment is as follows:
[0175] S1. Raw material preparation: Weigh a certain amount of perfluoropolyether diol, polyether polyol and toluene diisocyanate. The mass ratio of perfluoropolyether diol to polyether polyol is 1:2.5. The amount of toluene diisocyanate is 1.3 times the total mass of perfluoropolyether diol and polyether polyol.
[0176] S2. Prepolymerization reaction: Perfluoropolyether diol and polyether polyol are added to a three-necked flask and heated to 85°C under nitrogen protection. The mixture is stirred until it melts and is mixed evenly. Then, toluene diisocyanate is slowly added dropwise and the mixture is reacted at 85°C for 2.5 hours to obtain the prepolymer.
[0177] S3. Chain extension reaction: Cool the prepolymer to 55°C, add chain extender 1,4-butanediol, the amount of which is 12.5% of the prepolymer mass, and continue the reaction for 1.5 hours to further polymerize the prepolymer and obtain perfluoropolyether-polyurethane copolymer.
[0178] The preparation method of the graphene-carbon nanotube composite conductive filler in this embodiment is as follows:
[0179] S1. Dispersion of graphene and carbon nanotubes: Weigh a certain amount of graphene and carbon nanotubes respectively, add them to N,N-dimethylformamide at a mass ratio of 2:1, and ultrasonically disperse them in an ultrasonic cleaner at a frequency of 45kHz for 1.5 hours to obtain a uniform graphene dispersion and carbon nanotube dispersion.
[0180] S2. Composite reaction: The graphene dispersion and carbon nanotube dispersion were mixed and stirred at 175 r / min for 2.5 hours at 65℃ to fully composite the graphene and carbon nanotubes. Then, the mixture was filtered and washed four times with N,N-dimethylformamide to remove unreacted impurities. Finally, the washed product was dried at 80-90℃ for 2.5 hours to obtain the graphene-carbon nanotube composite conductive filler.
[0181] The preparation method of the waterproof and oil-resistant modified rubber sheath material in this embodiment is as follows:
[0182] S1. Plasticizing: Place nitrile rubber and fluororubber into a plasticizing machine and plasticize at 95°C for 7 minutes to give the rubber a certain degree of plasticity.
[0183] S2. Mixing: Place the plasticized rubber into a mixer and add nano-titanium boride-silane composite modifier, perfluoropolyether-polyurethane copolymer, graphene-carbon nanotube composite conductive filler, fast-extrusion carbon black, nano-calcium carbonate, dibutyl phthalate, and dioctyl sebacate in sequence. Mix at 85°C for 9 minutes to ensure that all raw materials are fully and evenly mixed.
[0184] S3. Add vulcanization system and antioxidant: Add zinc oxide, sulfur, accelerator DM, accelerator TMTD, antioxidant MB, and antioxidant 4010NA to the internal mixer and continue mixing for 4 minutes to ensure that the vulcanization system and antioxidant are evenly dispersed in the rubber.
[0185] S4, thin pass and calendering: The mixed rubber is put into the open mill and thin pass 6 times, and then calendered into sheet of the required thickness by a three-roll calender.
[0186] S5. Vulcanization: The calendered sheet is placed in a flat vulcanizing machine and vulcanized for 9 minutes at 165℃ and 11MPa to obtain a waterproof and oil-resistant modified rubber sheath material.
[0187] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.
[0188] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A waterproof and oil-resistant modified rubber sheath material, characterized in that, The composition includes the following parts by weight: Nitrile rubber: 80-100 parts; Fluororubber: 20-30 parts; Nano-titanium boride-silane composite modifier: 5-10 parts; Perfluoropolyether-polyurethane copolymer: 8-15 parts; Graphene-carbon nanotube composite conductive filler: 3-6 parts; Zinc oxide: 3-5 parts; Sulfur: 1-2 parts; Accelerator DM: 1-2 parts; Accelerator TMTD: 0.5-1 part; Quickly press out carbon black: 15-20 parts; Nano calcium carbonate: 10-15 parts; Dibutyl phthalate: 8-12 parts; Dioctyl sebacate: 5-8 parts; Anti-aging agent MB: 0.5-1 part; Anti-aging agent 4010NA: 0.5-1 part.
2. The waterproof and oil-resistant modified rubber sheath material according to claim 1, characterized in that, The preparation method of the nano-titanium boride-silane composite modifier is as follows: S1. Pretreatment of nano-titanium boride: Place nano-titanium boride powder in an oven and dry it at 100-120℃ for 2-3 hours to remove surface moisture; S2. Preparation of silane solution: Weigh a certain amount of γ-aminopropyltriethoxysilane and add it to anhydrous ethanol to prepare a silane solution with a mass fraction of 5%-10%. S3. Composite Modification: The pretreated nano-titanium boride powder is slowly added to a silane solution at a solid-liquid ratio of 1:
10. The mixture is stirred at 200-300 r / min for 3-4 hours at 50-60℃ to allow the silane to be fully adsorbed onto the surface of the nano-titanium boride. Then, the mixture is filtered and washed 3-5 times with anhydrous ethanol to remove unreacted silane. Finally, the washed product is dried at 80-90℃ for 2-3 hours to obtain the nano-titanium boride-silane composite modifier.
3. The waterproof and oil-resistant modified rubber sheath material according to claim 1, characterized in that, The preparation method of the perfluoropolyether-polyurethane copolymer is as follows: S1. Raw material preparation: Weigh a certain amount of perfluoropolyether diol, polyether polyol and toluene diisocyanate. The mass ratio of perfluoropolyether diol to polyether polyol is 1:2-3. The amount of toluene diisocyanate used is 1.2-1.5 times the total mass of perfluoropolyether diol and polyether polyol. S2. Prepolymerization reaction: Add perfluoropolyether diol and polyether polyol to a three-necked flask, heat to 80-90℃ under nitrogen protection, stir to melt and mix evenly; then, slowly add toluene diisocyanate, react at 80-90℃ for 2-3 hours to obtain the prepolymer; S3. Chain extension reaction: Cool the prepolymer to 50-60℃, add chain extender 1,4-butanediol, the amount of which is 10%-15% of the prepolymer mass, and continue the reaction for 1-2 hours to further polymerize the prepolymer and obtain perfluoropolyether-polyurethane copolymer.
4. The waterproof and oil-resistant modified rubber sheath material according to claim 1, characterized in that, The preparation method of the graphene-carbon nanotube composite conductive filler is as follows: S1. Dispersion of graphene and carbon nanotubes: Weigh a certain amount of graphene and carbon nanotubes respectively, add them to N,N-dimethylformamide at a mass ratio of 2:1, and ultrasonically disperse them in an ultrasonic cleaner at a frequency of 40-50kHz for 1-2 hours to obtain a uniform graphene dispersion and carbon nanotube dispersion. S2. Composite reaction: Mix the graphene dispersion and the carbon nanotube dispersion, and stir at 150-200 r / min for 2-3 hours at 60-70℃ to fully composite the graphene and carbon nanotubes; then, filter the mixture and wash it 3-5 times with N,N-dimethylformamide to remove unreacted impurities; finally, dry the washed product at 80-90℃ for 2-3 hours to obtain the graphene-carbon nanotube composite conductive filler.
5. A waterproof and oil-resistant modified rubber sheath material as described in any one of claims 1-4, characterized in that, The preparation method of the waterproof and oil-resistant modified rubber sheath material is as follows: S1. Plasticizing: Place nitrile rubber and fluororubber into a plasticizing machine and plasticize at 90-100℃ for 5-8 minutes to give the rubber a certain degree of plasticity. S2. Mixing: Place the plasticized rubber into a mixer and add nano-titanium boride-silane composite modifier, perfluoropolyether-polyurethane copolymer, graphene-carbon nanotube composite conductive filler, fast-extrusion carbon black, nano-calcium carbonate, dibutyl phthalate, and dioctyl sebacate in sequence. Mix at 80-90℃ for 8-10 minutes to ensure that all raw materials are fully and evenly mixed. S3. Add vulcanization system and antioxidant: Add zinc oxide, sulfur, accelerator DM, accelerator TMTD, antioxidant MB, and antioxidant 4010NA to the internal mixer and continue mixing for 3-5 minutes to ensure that the vulcanization system and antioxidant are evenly dispersed in the rubber. S4, thin pass and calendering: The mixed rubber is put into the open mill for thin pass 5-7 times, and then calendered into sheet of the required thickness by a three-roll calender. S5. Vulcanization: Place the calendered sheet into a flat vulcanizing machine and vulcanize it for 8-10 minutes at 160-170℃ and 10-12MPa to obtain waterproof and oil-resistant modified rubber sheath material.